Pengembangan Aplikasi Mobile Learning Pembelajaran Pendidikan Agama Buddha Kelas IV SD - Suryana, Ari; Walyono; Ratna Setyaningsih (Study program PGSD FKIP Universitas Bung Hatta, 2023)
This research and development aim to 1) developing mobile learning application on tolerance in culture of Buddhist Education subjects, 2) knowing the quality of the mobile learning application by validity, practicality, and effectivity of the product. This research and development are done by using Four-D model which consists of define, design, develop, and disseminate. The develop stage using multimedia development life cycle of six stages, which are concept, design, material collecting, assembly, testing, and distribution. The validity of the product by assessment of material experts and media experts resulting V score of 0,9 that means valid. The practicality of the product by assessment of the students resulting k score of 0,86 which is very practical. The effectivity of the product is conducted by doing test in experimental class and control class resulting N Gain score of experimental class is 77,27% in category effective in conclusion the mobile learning application is valid, practical, and effective.